2017
DOI: 10.1371/journal.pone.0184075
|View full text |Cite
|
Sign up to set email alerts
|

An acute bout of localized resistance exercise can rapidly improve inhibitory control

Abstract: The positive effect of acute resistance exercise on executive function, such as inhibitory control (IC), is poorly understood. Several previous studies have demonstrated this effect using whole-body resistance exercise. However, it remains unclear whether localized resistance exercise performed using only limited muscle groups could also acutely improve IC. Thus, the present study examined the effect of an acute bout of localized resistance exercise on IC. Twelve healthy men performed a color-word Stroop task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(75 citation statements)
references
References 44 publications
(77 reference statements)
3
70
0
Order By: Relevance
“…In total 71 papers were eligible for this review and meta-analysis. Overall, 44 studies (Aguirre-Loaiza et al, 2019;Akatsuka et al, 2015;Basso et al, 2015;Benzing et al, 2016;Browne et al, 2016;Budde et al, 2010Budde et al, , 2008Chang & Etnier, 2009;Chang et al, 2011;Coles & Tomporowski, 2008;Cooper et al, 2016Cooper et al, , 2012ÉW et al, 2011;Guzmán & López-García, 2016;Hwang et al, 2016;Hwang & Lu, 2018;Jaffery et al, 2018;Lambourne, 2012;Lambourne et al, 2010;Mezcua-Hidalgo et al, 2019;Moore et al, 2012;Murray & Russoniello, 2012;Palmiere et al, 2018;Peruyero et al, 2017;Pontifex et al, 2009;Prashanth, 2020;Du Rietz et al, 2019;Schwarck et al, 2019;Sipavičienė et al, 2012;Sperlich et al, 2018;Takahashi et al, 2019;Tine, 2014;Tine & Butler, 2012;Tsai et al, 2014Tsai et al, , 2016Tsorbatzoudis et al, 1998;Tsukamoto et al, 2017;Van den Berg et al, 2018;Vonk et al, 2019;Wang et al, 201...…”
Section: Resultsmentioning
confidence: 99%
“…In total 71 papers were eligible for this review and meta-analysis. Overall, 44 studies (Aguirre-Loaiza et al, 2019;Akatsuka et al, 2015;Basso et al, 2015;Benzing et al, 2016;Browne et al, 2016;Budde et al, 2010Budde et al, , 2008Chang & Etnier, 2009;Chang et al, 2011;Coles & Tomporowski, 2008;Cooper et al, 2016Cooper et al, , 2012ÉW et al, 2011;Guzmán & López-García, 2016;Hwang et al, 2016;Hwang & Lu, 2018;Jaffery et al, 2018;Lambourne, 2012;Lambourne et al, 2010;Mezcua-Hidalgo et al, 2019;Moore et al, 2012;Murray & Russoniello, 2012;Palmiere et al, 2018;Peruyero et al, 2017;Pontifex et al, 2009;Prashanth, 2020;Du Rietz et al, 2019;Schwarck et al, 2019;Sipavičienė et al, 2012;Sperlich et al, 2018;Takahashi et al, 2019;Tine, 2014;Tine & Butler, 2012;Tsai et al, 2014Tsai et al, , 2016Tsorbatzoudis et al, 1998;Tsukamoto et al, 2017;Van den Berg et al, 2018;Vonk et al, 2019;Wang et al, 201...…”
Section: Resultsmentioning
confidence: 99%
“…In each condition, five sets were conducted and in DT the load of the barbell was set to of 40% of 1-RM. We choose 40% of 1-RM because it was shown that even this low load leads to cognitive improvements [27]. As cognitive task, we used the serial subtraction of 7's from a three-digit number [28].…”
Section: Methodsmentioning
confidence: 99%
“…(3) On the behavioral/socioemotional level, established questionnaires such as “Felt Arousal Scale” [ 261 ], “Ratings of perceived exertion” [ 262 ], “Visual Analogue Scales” (e.g., to assess motivation or mental fatigue) [ 172 , 263 , 264 , 265 ], “SF-36” (to assess physical and mental components of the quality of life) [ 266 ] and “Pittsburgh Sleep Quality Index” (to assess various components of the sleep quality) [ 267 ] which are widely used in exercise–research with a neuropsychological and behavioral/socioemotional focus [ 141 , 172 , 263 , 264 , 265 , 268 , 269 ], should be used to elucidate the (moderating) effects of socioemotional states.…”
Section: Resistance Training With Blood Flow Restriction—an Added mentioning
confidence: 99%